A study on the correlation analysis between digitalization and Korean maritime listed firm performance - Han-Seon Park; Young Gyun Ahn (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
Due to the COVID-19 pandemic, the maritime industry has the task of enhancing its performance. Examining if the digitalization of maritime firms can encourage maritime sector optimization in the digital era is required. Based on data from a sample of Korean-listed maritime firms from 2010 to 2023, this paper discovers that digitalization can enhance firms’ financial and non-financial performance, mainly financial performance when faced with COVID-19. This influence works mainly through the impacts of business diversification, including extent and willingness, while it is more noticeable for willingness.